Pengaruh Budaya dan AgamaTerhadap Sains Sebuah Survey Kritis - Mohammad Muslih (TSAQAFAH, 2010)
This article does a thorough investigation into the bases underlying the development of science. This critical investigation starts on scientism view of its objectivism and universalism, and its consequence on the resulted style and model of scientific structure. The critical investigation here is not merely on logical and sociological consequences on development of science, but also on logical mind behind those claims. In more detail, this article shows that development of science in not solely based on scientific logic and epistemology, but also on sociological-historical and anthropological bases. In addition, the recent development indicates the existence of theological basis. As the result, it advocates the view that science is human construction and then cannot be sterile from human elements and factors surrounding the process of science development such as subjectivity, various interests, ideology and beliefs of scientific community. Academically, this article contributes in showing the importance of philosophy of science studies to see critically the way of sciences viewing the reality as the object of study, and to explore its field limits.